Branding is a Key to Going Network: a Case Study of Prambors Network - Singarimbun, Kartika; Karlinah, Siti; Darwis, Yuliandre; Rahmat Hidayat, Dadang (International Journal of Engineering and Technology, 2018)
Digital technology confiscates the listener, with the result that the attention of media audiences shifts. Radio expenditure below 1% since 2009. The company rivalry is raised as radio format is dominated by young people. This study has two major purposes are to investigate radio company which stands out in the stagnant of Indonesian radio broadcasting industry and the reason behind building a radio network. The subject of this study was Prambors radio network as the largest radio firm a step forward than any other in Indonesia. In-depth interviews were conducted with the Prambors's radio founder, employees and local radio partners. This study used an integrated marketing communications as the cross-communications process. This paper contributes to the current Indonesian radio industry where the findings indicate that radio network becomes an alternative corporate strategy. Prambors' brand programs have engaged positively local radio partners. A strong and positive brand name is the key to build radio network. Radio network can strengthen the company's position as its wide reach and can embrace more listeners. This original work contributed to the development of media management, especially radio and public relations studies.